Glioma-targeted delivery of exosome-encapsulated antisense oligonucleotides using neural stem cells - Tomasz Adamus; Chia-Yang Hung; Chunsong Yu; Elaine Kang; Mohamed Hammad; Linda Flores; Sergey Nechaev; Qifang Zhang; Joanna Marie Gonzaga; Kokilah Muthaiyah; Piotr Swiderski; Karen S. Aboody; et al. (Elsevier, 2022)
Tropism of neural stem cells (NSCs) to hypoxic tumor areas provides an opportunity for the drug delivery. Here, we demonstrate that NSCs effectively transport antisense oligonucleotides (ASOs) targeting oncogenic and tolerogenic signal transducer and activator of transcription 3 (STAT3) protein into glioma microenvironment. To enable spontaneous, scavenger receptor-mediated endocytosis by NSCs, we used previously described CpG-STAT3ASO conjugates. Following uptake and endosomal escape, CpG-STAT3ASO colocalized with CD63+ vesicles and later with CD63+CD81+ exosomes. Over 3 days, NSCs secreted exosomes loaded up to 80% with CpG-STAT3ASO. Compared to native NSC exosomes, the CpG-STAT3ASO-loaded exosomes potently stimulated immune activity of human dendritic cells or mouse macrophages, inducing nuclear factor κB (NF-κB) signaling and interleukin-12 (IL-12) production. Using orthotopic GL261 tumors, we confirmed that NSC-mediated delivery improved oligonucleotide transfer from a distant injection site into the glioma microenvironment versus naked oligonucleotides. Correspondingly, the NSC-delivered CpG-STAT3ASO enhanced activation of glioma-associated microglia. Finally, we demonstrated that NSC-mediated CpG-STAT3ASO delivery resulted in enhanced antitumor effects against GL261 glioma in mice. Peritumoral injections of 5 × 105 NSCs loaded ex vivo with CpG-STAT3ASO inhibited subcutaneous tumor growth more effectively than the equivalent amount of oligonucleotide alone. Based on these results, we anticipate that NSCs and NSC-derived exosomes will provide a clinically relevant strategy to improve delivery and safety of oligonucleotide therapeutics for glioma treatment.